2020
DOI: 10.3399/bjgpopen20x101153
|View full text |Cite
|
Sign up to set email alerts
|

GP decisions to participate in emergencies: a randomised vignette study

Abstract: Background Little is known about how General Practitioners (GPs) decide whether to participate in emergencies. Aim To test whether GPs participation is associated with cause of symptoms, distance to the patient, other patients waiting and out of hours (OOH) clinic characteristics. Design and Setting Online survey to all Norwegian GPs (n = 4701). Method GPs were randomised to vignettes describing a patient with acute shortness of breath and asked if they would participate in a call-out. The vignettes varied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…21 papers, (11,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and one correction, (34) were accepted for data extraction and quality appraisal. The characteristics of included papers are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 papers, (11,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and one correction, (34) were accepted for data extraction and quality appraisal. The characteristics of included papers are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Emergency medical technicians felt such training should be mandatory for GPs in EMS, and GPs appreciated the opportunity to train together. (15)(16)(17)30) Based on cases encountered by GPs in rural EMS, where GPs in Norway are more likely to play a role than in urban areas, (25) a Norwegian study suggested that GPs working in EMS should be competent in "fundamental, practical procedures". These included venous cannulation, intravenous drug administration, administering oxygen, and recording and monitoring of an ECG.…”
Section: Staff Factorsmentioning
confidence: 99%